Mentoring Matters: Mentoring as Collaborative Effort - McCann, Thomas M. (English journal, 2010)
When given the opportunity to work with mentor programs in schools, this author has recommended a global prescription for mentors to help new teachers make the transition into the world of teaching: encourage them to follow the practices that are most like those of good, experienced teachers. Experienced teachers are different from new teachers; the veterans have many advantages that come with experience. But how can new teachers gain some of the advantages of experience without actually experiencing years of teaching? The author summarizes some of the distinctive advantages that come with experience and suggests how collaborative approaches to teaching promote some of those advantages.